Pronaf: Observaç\~oes sobre o programa e desafios futuros - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The Small Farming National Support Program (Pronaf) was established by Resolution No. 2.191 in 1995. Here, the goal was to conduct a non-exhaustive review of the Program, focusing on potential improvements and further evaluations of the Program. Eighty published studies from 2019 and 2023 were selected, including theses, dissertations, and academic papers. These analyses encompass institutional evaluations, qualitative analyses, and case studies. The main finding is the crucial role of articulated financial support, cooperative initiatives, improved access to rural extension and technical assistance, and enhancements to the farmers' training and education.
Keywords: Q10; Q18; 330; agriculture and cattle; Brazil; Pronaf